Group B Streptococcus: developing a correlate of protection for a vaccine against neonatal infections. Issue 3 (June 2016) - Dangor, Ziyaad; Lala, Sanjay G.; Kwatra, Gaurav; Madhi, Shabir A.
Abstract : Purpose of review: Maternal vaccination to prevent invasive Group B Streptococcus (GBS) disease in infants is an important alternative strategy to intrapartum antibiotic prophylaxis. Licensure of GBS vaccines could be expedited using immunological correlates of protection. Recent findings: Between 2014 and 2015, we identified two studies that demonstrated an inverse association between invasive GBS disease and maternal serotype III capsular antibody levels greater than 1 μg/ml and greater than 3 μg/ml, and higher maternal antibody levels were associated with protection against serotype Ia disease. Furthermore, serotype Ia and III antibody levels greater than 3 μg/ml were associated with a reduced risk of GBS colonization in pregnant women. Experimental studies have investigated the use of GBS surface proteins as vaccine candidates. Although the immunogenic potential of pilus island and other surface proteins has been shown in animal-model studies, no association between maternal pilus island antibody levels and invasive GBS disease was demonstrated in infants. Additionally, several novel innate immune mediators that prevent GBS infection have been described in human and experimental studies. Summary: Recent studies suggest that maternal capsular antibody thresholds may be used as immunological correlates of protection for vaccine licensure. Surface proteins, as candidate vaccines or conjugates to the polysaccharide-protein vaccine, may broaden protection against invasive GBS disease.